Supply-Chain Survival in the Age of Globalization - Pope, James A (Business Expert Press, 2011)
Ebook from IG Library ; The purpose of this book is to trace the history of globalization and its impact on supply chain management and to look at the problems and some of the solutions facing global supply chains in the current era. The current challenge is surviving the challe.